Oligometastatic breast cancer and metastasis-directed treatment: an aggressive multimodal approach to reach the cure - Filippo Merloni; Michela Palleschi; Chiara Casadei; Antonino Romeo; Annalisa Curcio; Roberto Casadei; Franco Stella; Giorgio Ercolani; Caterina Gianni; Marianna Sirico; Simona Cima; Samanta Sarti; et al. (Therapeutic Advances in Medical Oncology, 2023)
Metastatic breast cancer (BC) is considered an incurable disease and is usually treated with palliative intent. However, about 50% of metastatic BCs present with only a few metastatic lesions and are characterized by longer overall survival. These patients, defined as oligometastatic, could benefit from a multimodal approach, which combines systemic therapy with metastasis-directed treatment (stereotactic ablative therapy or surgery). The current definition of oligometastatic seems incomplete since it is based only on imaging findings and does not include biological features, and the majority of relevant data supporting this strategy comes from retrospective or non-randomized studies. However, the chance of reaching long-term complete remission or even a cure has led to the development of randomized trials investigating the impact of combined treatment in oligometastatic BC (OMBC). The SABR-COMET trial, the first randomized study to include BC patients, showed promising results from a combination of stereotactic ablative radiotherapy and systemic therapy. Considering the randomized trial’s results, multidisciplinary teams should be set up to select OMBC patients who could achieve long-term survival with aggressive multimodal treatment.